2014
DOI: 10.1097/gme.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of increased interleukin-17A serum levels in postmenopausal estrogen deficiency

Abstract: The results demonstrate a high prevalence of increased serum IL-17A levels in postmenopausal estrogen deficiency, which can play an inducing role in chronic inflammatory events such as bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 21 publications
5
30
0
Order By: Relevance
“…In the meantime, we also found that serum IL-17A was negatively correlated with the T scores of lumbar spine BMD, which was consistent with the study findings by Ildiko'Molna'r et al [23]. Despite the very limited number of IL-17 studies in patients with osteoporosis, IL-17 studies in animal models and cell cultures supported our research findings.…”
Section: Discussionsupporting
confidence: 94%
“…In the meantime, we also found that serum IL-17A was negatively correlated with the T scores of lumbar spine BMD, which was consistent with the study findings by Ildiko'Molna'r et al [23]. Despite the very limited number of IL-17 studies in patients with osteoporosis, IL-17 studies in animal models and cell cultures supported our research findings.…”
Section: Discussionsupporting
confidence: 94%
“…The change in circulating IL-17 level in the context of estrogen deprivation was frequently reported in animal studies [18] . Our study observed a significant rise in circulating IL-17 level in osteoporotic postmenopausal women, which was consistent with recent findings [19,25,26] . IL-17 can directly promote the production of RANKL by osteoblasts [17,18,27,28] .…”
Section: Discussionsupporting
confidence: 82%
“…Another factor responsible for the bone loss induced by estrogen deficiency is IL-17, the signature cytokine of Th17 cells (47), which are an osteoclastogenic subset of CD4 + T cells (45,46). Intriguingly, postmenopausal women with osteoporosis exhibit elevated levels of serum IL-17 (66)(67)(68). In mice, ovx expands Th17 cells by promoting the differentiation of naive CD4 + T cells into mature Th17 cells (69), a phenomenon driven by cytokines such as TGFβ, IL-6, IL-1β, and TNF (43,44,47,70) -factors that are all disregulated by estrogen deficiency (25).…”
Section: Discussionmentioning
confidence: 99%